Sosialisasi Perlindungan Korban Kekerasan dalam Rumah Tangga Bersama DP3AKB Kota Balikpapan - Made Erinda Putri Fricilla; Nurul Annisa (Politeknik Piksi Ganesha Indonesia, 2026)
Gender- based domestic violence, also known as domestic violence, usually occurs in the private sphere, where the perpetrator is someone known to and close to the victim. For example, husbands beat their wives, fathers abuse their children, uncles molest their nephews, grandfathers hit their grandchildren, and so on. The Balikpapan University community service team carried out a work program in Gunung Samarinda Baru Village with the title Socialization of Protection for Victims of Domestic Violence. To overcome this problem, the Balikpapan University KKN group invited the Women's Empowerment Service, Child Protection, and Family Planning as a resource person. This outreach was aimed at PKK mothers in Gunung Samarinda Baru Village. The aim of this outreach is to give them knowledge about what they should do if domestic violence occurs.